Approaches of selecting international entry modes for Chinese household appliances companies to conduct internationalization in UK: The case of Midea - Wang, Can (2016)
Recent years, Chinese household appliances companies have been developing well in the world. In order to obtain huge performance in the world, conducting internationalization in powerful countries like UK is necessary. Through the internationalization, firms are able to expand their benefits, and enlarge their influence, so selecting an appropriate entry mode is very critical. But there are several methods for companies to choose entry modes, and it is unsure that whether existing approaches are suitable for selecting entry modes for Chinese household appliances companies. As a result, the aim of this dissertation is analysing four main existing popular approaches to examine that whether they are good for Chinese home appliances firms to select entry modes. In this dissertation, case study will be used, because it is impossible to research all Chinese companies in a limited time period. Through the analysis of the chosen case - Midea, some findings would be gained. The result shows that those four existing approaches cannot help Chinese household appliances firms select an appropriate entry mode, because each way focuses only one perspective, and they are not comprehensive. Therefore, the combination of those principal approaches would be more comprehensive, and would be possibly suitable for Chinese household appliances companies. There is limitation in this study, for example, the result is likely only suitable for the researching field, and the result needs change after a certain period, because some components utilized to examine approaches are changeable. Moreover, in the future, it will be likely that there are some new factors influencing the selection, so the result should change accordingly.